Chloroplast arrangement as a factor of photosynthesis in multilayered leaves - Z. Lechowski (Acta Societatis Botanicorum Poloniae, 2015)
The dependence of photosynthesis on arrangement of the chloroplasts in Ajuga reptans and Syringa vulgaris differing in the ability of chloroplasts translocation was studied.